2010
DOI: 10.3233/jvr-2010-0507
|View full text |Cite
|
Sign up to set email alerts
|

Roles and functions of benefits counseling specialists: A multi-trait analysis

Abstract: The purpose of this study is to examine the roles and functions of benefits counseling specialists. One-hundred and forty-eight benefits counseling specialists rated the Benefits Specialists Practice Inventory -Revised using a 5-point importance rating scale. Data were analyzed using multi-trait analysis. The multi-trait analysis tentatively supported the three-factor structure of the Benefits Specialists Practice Inventory -Revised, indicating that benefits screening (M = 4.43, SD = 0.47), benefits advisement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…As youth and family members work, they may need help navigating the youth and family member public benefits. Work incentive benefits counseling (WIBC) provides informed choice to individuals on how employment income and savings will impact their disability monetary and health benefits (Lui et al, 2010). WIBC is significantly related to increases in beneficiary work and earnings (Delin, Hartman, & Sell, 2012;Kregel, 2012;Schimmel, O'Day, Roche, Livermore, & Harris, 2010;Tremblay, Smith, Xie, & Drake, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As youth and family members work, they may need help navigating the youth and family member public benefits. Work incentive benefits counseling (WIBC) provides informed choice to individuals on how employment income and savings will impact their disability monetary and health benefits (Lui et al, 2010). WIBC is significantly related to increases in beneficiary work and earnings (Delin, Hartman, & Sell, 2012;Kregel, 2012;Schimmel, O'Day, Roche, Livermore, & Harris, 2010;Tremblay, Smith, Xie, & Drake, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Transition-age youth with autism spectrum disorders and learning disabilities both had higher rates of competitive integrated employment when connecting with vocational rehabilitation services (Kaya et al, 2016). Work incentives benefits counseling provided in conjunction with VR services should be considered a necessary intervention for all people seeking employment who are receiving Social Security Disability Insurance (SSDI), SSI, or public medical benefits such as Medicaid or Medicare (Hartman et al, 2015;Leahy et al, 2014;Lui et al, 2010). Work incentive benefits counseling has been shown to improve employment outcomes for individuals with disabilities by increasing their employment rates and income (Delin et al, 2012;Hartman et al, 2015;Leahy et al, 2014;Tremblay et al, 2004;.…”
Section: Work Incentives Benefits Counselingmentioning
confidence: 99%
“…A number of factors, including: poverty, globalization, unemployment rate, employer attitudes, and perceived loss of benefits, contribute to the disparity in employment rates between these two groups of individuals (Baldwin, 1999;Bernell, 2000;Burkhauser, Houtenville, & Wittenburg, 2003;Switzer, 2003). Research has shown that many individuals with disabilities want to work in competitive integrated employment but may be afraid of losing public benefits as a result of increased employment activity and income (Hartman, Anderson, Chan, Fried, & Lui, 2015;Lui et al, 2010;McDonough & Revell, 2010;Tremblay, Smith, Xie, & Drake, 2006). Those receiving SSA benefits frequently do not understand how employment will change their benefits or may be unacquainted with the work incentives already built into SSA programs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations